Psychometric evaluation of the German version of the Recovering Quality of Life (ReQoL) measures in patients with affective disorders - Thomas Grochtdreis; Hans-Helmut König; Anju Devianee Keetharuth; Jürgen Gallinat; Alexander Konnopka; Holger Schulz; Martin Lambert; Anne Karow; Judith Dams (The European Journal of Health Economics, 2022)
Background: The generic self-reported Recovering Quality of Life (ReQoL) measures were developed for measuring recovery-focused health-related quality of life (HrQoL) in persons with mental health conditions. The aim of this study was to assess the psychometric properties of the German version of the ReQoL measures in patients with affective disorders in Germany. Methods: Data from a patient sub-sample in a randomized controlled trial have been used ( N 0.167em=0.167em393). The internal consistency and the test–retest reliability of the ReQoL measures were assessed using Cronbach's Alpha and the intra-class correlation coefficient (ICC). The concurrent validity and the known-group validity of the ReQoL measures were assessed using Pearson's Correlation coefficient and Cohen's d. The responsiveness was assessed using Glass' Δ and the standardized response mean (SRM). Results: The reliability among the items of the ReQoL-20 was overall excellent. The ICC of the ReQoL-20 was r 0.167em=0.167em0.70, indicating moderate test–retest reliability. The concurrent validity of the ReQoL-20 with the clinical measure PHQ-9 was strong with a correlation coefficient of r 0.167em=0.167em-0.167em0.76. The known-group validity of the ReQoL-20 using PHQ-9 cut-off points was large with an effect size of d 0.167em=0.167em1.63. The ReQoL measures were sensitive to treatment~response and remission~of symptoms measured by the PHQ-9 with large effect sizes/SRM. Discussion: The psychometric properties of the ReQoL measures for the assessment of patients with affective disorders were overall good. With the ReQoL, valid and reliable measures for the assessment of recovery-focused HrQoL for persons with affective disorders are available in German language.
Keywords: I10; I30; 610; Reliability; Validity; Responsiveness; EQ-5D; SF6D; Health-related quality of life; Mood disorders; Germany